The variation of the fine structure constant: an update of statistical analysis with recent data - Kraiselburd, Lucila (2013)
Aims. We analyze different astronomical data of the variation in the fine structure constant obtained with KECK and VLT to check their consistency.Methods. We test consistency using the Student test and confidence intervals. We split the data sets in smaller intervals and group them by i) redshift and ii) angular position. Another statistical analysis is proposed considering phenomenological models for the variation in alpha. Results. Results show consistency for reduced intervals for each pair of data sets considered and suggest that the variation in alpha is important at higher redshifts.Conclusions. Even though the ?dipole model? proposed by Webb et al. seems to be the most accurate phenomenological model, the statistical analyses indicates that the variation in might be depending both on redshift and angular position.